Effect of digital literacy on individual work performance among practicing lawyers in Malaysia / Ain Syahirah Abd Rahim ... [et al.] - Abd Rahim, Ain Syahirah; Baharuddin, Mohammad Fazli; Jalil, Abdurrahman; Mohd Amin, Zahari; Rahmad, Fadhilnor (Faculty of Information Management, 2023)
Working industry adapting the changes in working environment are influenced by employee capabilities in adapting new situation especially involving the technology. Law practitioner's fields are also affected from the change of how the industry works. Work wise, this transition gives an impact to the performance in term of facilities and evaluation of accurate legal materials. This study investigated the effect of digital literacy on individual work performance among practicing lawyers in Malaysia. The data was collected from 271 respondents which were extracted into statistics testing using Statistical Package for the Social Science (SPSS) and Partial Least Squares Structural Equation Modelling (SmartPLS). The results revealed that the independent variables, namely technical skill, cognitive skill and social-emotional skill, influenced individual work performance. This paper provides in depth discussion on significant relationship between digital literacy and individual work performance among the practicing lawyers in Malaysia.